IDENTIFIKASI TITIK KRITIS KEHALALAN GELATIN - Sri Endang; Aji Jumiono; Syahrir Akil (Jurnal Ilmiah Pangan Halal, 2020)
Gelatin is a substance obtained from partial hydrolysis of collagen from skin, white connective tissue and animal bones. The halal status of gelatin is certainly determined by the type of gelatin source, if it is made of halal animal skin or bones such as cow, buffalo, goat, sheep, then the halal status of gelatin is influenced by the method of slaughtering the animal. If the slaughter is in accordance with the provisions of Islamic law, the source of the skin and bones used is halal. However, if it comes from skin or bones or mixed with pork, then the status is haram. If the source of the ingredients for making gelatin uses skin, fins and fish bones, this gelatin source is a halal material. To show the halal status of gelatin, a document in the form of a halal certificate is required. Gelatin, which in the numbering of food additives has the code E441, can be used for various purposes in processed food products such as hydrocolloids, capsule-making materials, fruit juice concentrating and purification, materials for making Marsmallow products and others. Gelatin can also be used as a filler, coating to coat the outside of a product that is unstable, resulting in peptone being used as a medium for growing microorganisms, and can also be used as an auxiliary material for the manufacture of ion-exchange resins. Another byproduct of the gelatin industry from bone is di-tricalsium phosphate.